Moral Education in the Era of Globalization for the Formation of a True Muslim Identity - Dewi Wijayanti, Euis; Abidin, Zainal; Komara, Endang; Mauludin, Hilman (PT Mattawang Mediatama Solution, 2024)
Moral education is essential and must be instilled from an early age, especially in the era of globalization for the formation of a true Muslim identity. A child's mental development continues to evolve and develop towards the perfection of his thinking. For this reason, at the Riyadlu As-Shalihin Cintaraja Integrated Islamic Boarding School, personality morals are the most important parameter. The aim of this research is to determine moral education in the era of globalization for the formation of a true Muslim identity at the Riyadlu As-Shalihin Cintaraja Integrated Islamic Boarding School. This research uses a qualitative approach, descriptive method, case and field design. As a result of his research, all habituation programs at the Riyadlu As-Shalihin Cintaraja Integrated Islamic Boarding School are recorded in the RAKAAT Book (Report of Activities for Taqwa Children) which is highly respected (1). Honesty, (2). Discipline. (3). Full of sincerity in carrying out devotion to worship. The contents of the Rak'at Book include; (1). Yaumiah Prayer Service Activities: Pardhu, Dhuha, Qiyamullail, witr prayers. (2). Tadarus Al-Qur'an activities, murojaah/Tahfidz juz 29, 30, and selected syura (Yaasin, Al-Mulk, Al-Wakiah, Al-Jumu'ah, al-Kahfi, Ar-Rahman). (3). Tabarat (afterlife savings) is a balance so that you don't only save for worldly interests, but also for the hereafter. Form of application of the program; (1). KETAWA program (if you find trash, take it straight away), (2). Makbul Program (anti-violence Madrasah). (3). Tablignatun Mubaligin” for learning to become a Da'i. The problems faced have been anticipated by the teachers/clerics/ustadzah as human resources at this Islamic boarding school, never to shift from the application of the Rakaat Book. It's simple, just carry out the rakat after the output. The solution is to maximize the running of the RAKAAT Book as well as good coordination between the school and the students' parents.